Development of Teaching Materials for Dance Music Courses Based on Project Based Learning Containing QR Codes - Irwansyah, Irwansyah; Prastiawan, Inggit (Gondang: Jurnal Seni dan Budaya, 2023)
This research aims to develop Project Based Learning-Based Teaching Materials containing QR Codes for the Dance Music course that are valid and effective in improving the learning outcomes of Dance and Performing Arts Study Program students. The research method used is development research with a 4D (Four-D) development model which consists of four stages, namely: 1) Define, 2) Design, 3) Development and 4) Disseminate. The data collection techniques that will be used are expert validation sheets, response questionnaires and student learning outcomes instruments. The results of this research are as follows (1) Producing Project Based Learning-Based Teaching Materials containing QR Codes in the Dance Music course which are suitable for use with an average percentage of expert validation results of 89.28% in the "very good" category while the percentage is average -The average in individual tests, small groups and limited field tests was 95.20% in the "very good" category. (2) The effectiveness of using teaching materials that have been developed in learning shows that there is a prominent difference between learning outcomes before using and after using teaching material products. This is based on data processing using the SPSS 20 application, obtained t count > t table or 42.32 > 2.05 with df =25, the learning outcomes after using teaching materials are 77.42% higher than the learning outcomes before using teaching materials which are 64.46%. So, it is concluded that the teaching materials developed are effective in improving student learning outcomes.